(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The objectives of this research were to study the home working production process and to study labour rights understanding of the home workers in the rural area of Khon Kaen province, Thailand via the qualitative research methodology. Data collection was based on an in-depth interview and observation to 18 home workers, which conducted during March August 2010. The content analysis was employed to data analysis. The results indicated that the formation of the home workers was driven by the demand from the producers from neighboring villages. These producers were operating within the chain of production associated with other producers from the central part. Due to their formation as a group, their existing skills in garment and tailoring, and their increased labor management skill, they had the ability to get order directly from the outside producers. Despite their limited negotiation capacity regarding benefits, the informal labours considered the home workers as economically rewarding and beneficial to their family. As regards understanding on the labour rights, the home workers define the labour rights as the right to social insurance, the right to safe work place, the right to medical services, and the right to increased wages. The majority of them had a limited understand about the labour rights as it was related to the rights and duty of the employees and employers.